2008
DOI: 10.1002/jmor.10668
|View full text |Cite
|
Sign up to set email alerts
|

The gross morphology and histochemistry of respiratory muscles in bottlenose dolphins, Tursiops truncatus

Abstract: Most mammals possess stamina because their locomotor and respiratory (i.e., ventilatory) systems are mechanically coupled. These systems are decoupled, however, in bottlenose dolphins (Tursiops truncatus) as they swim on a breath-hold. Locomotion and ventilation are coupled only during their brief surfacing event, when they respire explosively (up to 90% of total lung volume in approximately 0.3s) (Ridgway et al., 1969). The predominantly slow-twitch fiber profile of their diaphragm (Dearolf, 2003) suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 65 publications
0
64
0
Order By: Relevance
“…Because experimental data suggest that the expiratory phase of spontaneous breaths is a passive process, the animals remain stationary during this testing. Morphological, anatomical and observational data suggest that the expiratory phase of normal respiration while swimming is coupled with locomotion and physical posturing (Cotten et al, 2008). We acknowledge that spontaneous breaths decoupled from locomotion may not represent the exact phenomenon of respiration while swimming.…”
Section: Discussionmentioning
confidence: 88%
“…Because experimental data suggest that the expiratory phase of spontaneous breaths is a passive process, the animals remain stationary during this testing. Morphological, anatomical and observational data suggest that the expiratory phase of normal respiration while swimming is coupled with locomotion and physical posturing (Cotten et al, 2008). We acknowledge that spontaneous breaths decoupled from locomotion may not represent the exact phenomenon of respiration while swimming.…”
Section: Discussionmentioning
confidence: 88%
“…For example, it has been suggested that the diaphragm and intercostal muscles are important to generate high respiratory flow and rapid f R (Ridgway, 1972;Dearolf, 2003;Cotten et al, 2008). However, few studies have compared the functional properties within and between species.…”
Section: Respiratory Mechanics: Flow and Compliancementioning
confidence: 99%
“…Dearolf et al, 2000;Etnier et al, 2004;Cotten et al, 2008;Kielhorn et al, 2013), were used. Approximately 1cm 3 blocks of m. longissimus dorsi were cut from a position just ventral to the superficial tendon (Pabst, 1990), coated with Optimal Cutting Temperature compound (Sakura Finekek, Torrance, CA, USA), rapidly frozen in isopentane cooled by liquid nitrogen, and sectioned at 10μm thickness in a cryostat (Leica Microsystems, Wetzlar, Germany) at −19°C.…”
Section: Muscle Histochemistry and Fiber Diametermentioning
confidence: 99%